2020
DOI: 10.5194/cp-2020-50
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Influence of temporally varying weatherability on CO<sub>2</sub>–climate coupling and ecosystem change in the late Paleozoic

Abstract: Abstract. Earth's penultimate icehouse, the Late Paleozoic Ice Age (LPIA), was a time of dynamic glaciation and repeated ecosystem perturbation, under conditions of substantial variability in atmospheric pCO2 and O2. Improved constraints on the evolution of atmospheric pCO2 and O2 : CO2 during the LPIA and its subsequent demise to permanent greenhouse conditions is crucial for better understanding the nature of linkages between atmospheric composition, climate, and ecosystem perturbation during this time. We p… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 72 publications
1
13
0
Order By: Relevance
“…The relationship between low-latitude kaolinite content in the study area and the high-latitude glacial cycles established 195 by previous studies is shown in Figure 9. The three higher kaolinite content intervals from S-I, S-III, and S-V are roughly isochronous with climate warming interglacial periods and are consistent with an increase of global atmospheric pCO2 (Richey et al, 2020;Fig. 9f) and high surface seawater temperatures (Korte et al, 2005;Grossman et al, 2008;Fig.…”
Section: Low-latitude Ncp Climate Change Linked To the High-latitude Glaciationsupporting
confidence: 59%
See 1 more Smart Citation
“…The relationship between low-latitude kaolinite content in the study area and the high-latitude glacial cycles established 195 by previous studies is shown in Figure 9. The three higher kaolinite content intervals from S-I, S-III, and S-V are roughly isochronous with climate warming interglacial periods and are consistent with an increase of global atmospheric pCO2 (Richey et al, 2020;Fig. 9f) and high surface seawater temperatures (Korte et al, 2005;Grossman et al, 2008;Fig.…”
Section: Low-latitude Ncp Climate Change Linked To the High-latitude Glaciationsupporting
confidence: 59%
“…The Cisuralian (early Permian) represents the peak of the Late Paleozoic Ice Age (LPIA; ca. 332-260 Ma) in which significant shifts from glacial to interglacial conditions occurred in high-latitude Gondwana (e.g., Montañez et al, 2007;30 Fielding et al, 2008;Montañez and Poulsen, 2013;Garbelli et al, 2019;Richey et al, 2020). These glacial-interglacial events caused fluctuations in the global climate and are recorded by indirect proxies from mid-and low-latitudes in marine and continental deposits (e.g., Korte et al, 2005;Grossman et al, 2008;Davydov, 2014;Yang et al, 2016Yang et al, , 2020.…”
Section: Introductionmentioning
confidence: 99%
“…The three intervals with lower kaolinite content from S-II, S-IV, and S-VI roughly correspond to climate cooling glacial periods from glaciations P1 and P2 and the transition period to glaciation P3 in high latitudes. The intervals with lower 200 kaolinite content are also are isochronous with an interval of decreasing global atmospheric pCO2(Foster et al, 2017;Richey et al, 2020; Fig. 9f) and surface seawater temperatures(Korte et al, 2005; Fig.…”
mentioning
confidence: 79%
“…(a) Refined chronostratigraphy of Asselian and Sakmarian. (b) Low‐latitude paleosol‐carbonate‐based p CO 2 record (Montañez et al., 2007; Richey et al., 2020). (c) Record on Gondwana.…”
Section: Discussionmentioning
confidence: 99%
“…Reconstructed atmospheric p CO 2 indicates a stepwise rise from a minimum across the Carboniferous–Permian boundary to maximum concentrations toward the end of the Sakmarian (Montañez et al., 2007; Richey et al., 2020). A rise in p CO 2 would not only promote the demise of the DSIII in the Karoo Basin on Gondwana but also enhance surface evaporation to desiccate the low latitudes (Figures 9d–9f).…”
Section: Discussionmentioning
confidence: 99%